Dark Trait Tetrad and Online Deception in Tiktok users - Farooq, Rabia; Ashraf, Rabbia (Applied Psychology Review, 2022)
The research aimed to assess the relationship between dark trait tetrad and online deception in TikTok users. It was hypothesized that there is a significant positive relationship between dark tetrad and online deception. Furthermore, the dark tetrad may significantly predict online deception in TikTok users. Moreover, there is a gender difference in dark tetrad and online deception in TikTok users. Correlational research design and Purposive sampling technique were used to collect data. The sample comprised N = 100 TikTok users constituting both Men (n = 50) and Women (n = 50). Dark Tetrad Traits Scale, Measuring of Online Deception and Intimacy Scale (MODI) was used to assess the targeted study variables in TikTok users. The results revealed that there is a significant positive relationship between Dark Tetrad and Online Deception among TikTok users. The narcissism and sadism subscale of Dark Tetrad came out to be positive predictors of Online Deception in TikTok users. While the result of the independent sample t-test indicated non-significant gender differences in Dark Trait Tetrad and Online Deception. This study will help provide the basis for further empirical research, about the etiological reason for antisocial behavior.